2020
DOI: 10.2903/j.efsa.2020.5965
|View full text |Cite
|
Sign up to set email alerts
|

Update of the list of QPS‐recommended biological agents intentionally added to food or feed as notified to EFSA 11: suitability of taxonomic units notified to EFSA until September 2019

Abstract: Qualified presumption of safety (QPS) was developed to provide a generic safety evaluation for biological agents to support EFSA's Scientific Panels. The taxonomic identity, body of knowledge, safety concerns and antimicrobial resistance are assessed. Safety concerns identified for a taxonomic unit (TU) are where possible to be confirmed at strain or product level, reflected by ‘qualifications’. No new information was found that would change the previously recommended QPS TUs and their qualifications. The list… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 203 publications
(225 reference statements)
1
50
0
Order By: Relevance
“…The list is a reasonable basis for establishing safety of food strains when belonging to a QPS species, provided that the strain-specific testing described below is also conducted. The list results from historical data, from regular monitoring of the body of knowledge and through extensive scientific literature reviews, applied to a wide array of micro-organisms traditionally found in the food chain (EFSA, 2020b). It should be noted that the scope of QPS is food consumption by the general, healthy population and does not specifically take into consideration potential risks for vulnerable populations (EFSA, 2005) or non-food uses of probiotics.…”
Section: Probiotic Species and Strains Must Be Safe For Human Consumpmentioning
confidence: 99%
“…The list is a reasonable basis for establishing safety of food strains when belonging to a QPS species, provided that the strain-specific testing described below is also conducted. The list results from historical data, from regular monitoring of the body of knowledge and through extensive scientific literature reviews, applied to a wide array of micro-organisms traditionally found in the food chain (EFSA, 2020b). It should be noted that the scope of QPS is food consumption by the general, healthy population and does not specifically take into consideration potential risks for vulnerable populations (EFSA, 2005) or non-food uses of probiotics.…”
Section: Probiotic Species and Strains Must Be Safe For Human Consumpmentioning
confidence: 99%
“…According to the Food and Drug Administration, probiotic bacteria should "Generally be Recognized as Safe" [47]. In Europe, a "Qualified Presumption of Safety" is responsible for recommending biological agents intentionally added to food or feed, and information is available in the European Food Safety Authority scientific panels [48].…”
Section: Enterococci As Probioticsmentioning
confidence: 99%
“…Benyacoub et al [77] confirmed an immunomodulatory role of E. faecium SF68 on the intestinal mucosa and the development of the digestive system in young dogs. Another preparation, Cylactin ® , containing the strain E. faecium NCIMB 10415, has been used in pig and poultry farming as a feed additive in European Union countries instead of supplementary avoparcin to stimulate animal growth [46,48,78].…”
Section: The Probiotic Importance Of Enterococcus Spp and Applicationsmentioning
confidence: 99%
“…LAB are microaerophilic Gram-positive bacteria which play an important role in food fermentations but also include commensals of vertebrates and insects as well as pathogens [ 20 ]. Food fermenting LAB, particularly species grouped in the Lactobacillaceae , have a safe tradition of use in food [ 21 ], but this group also includes pathogens or opportunistic pathogens. For instance, Enterococcus faecium has evolved as vertebrate commensals and occur in food fermentations but specific lineages of E. faecium also are a leading cause of hospital-acquired infections with multi-drug resistant bacteria [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%